Visualization of Cytokinesis Events in Budding Yeast by Transmission Electron Microscopy - Meitinger, Franz; Pereira, Gislene (Yeast Cytokinesis, 2016)
In yeast cells, cytokinesis is accompanied by morphological changes due to cell wall growth during furrow ingression and abscission. The characteristics of the growing cell wall can be used as an indicator for the function of the contractile actomyosin ring, the Rho-GTPases Rho1 and Cdc42 and/or other factors that drive cytokinesis. The ultrastructural information of the cell wall can be easily acquired by transmission electron microscopy, which makes this technique an invaluable tool to analyze cell division in yeast cells. Here, we describe the process of embedding and staining budding yeast cells for transmission electron microscopic analysis of cytokinetic events.
Gesehen am 22.05.2017